2018
DOI: 10.1093/abbs/gmy086
|View full text |Cite
|
Sign up to set email alerts
|

MiR-147b influences vascular smooth muscle cell proliferation and migration via targeting YY1 and modulating Wnt/β-catenin activities

Abstract: Cardiovascular disease is the leading cause of death worldwide. Dysregulation of microRNAs (miRNAs) has been found to be associated with cardiovascular diseases such as atherosclerosis. In the present study, we examined the role of miR-147b in the proliferation and migration of vascular smooth muscle cells (VSMCs). Quantitative real-time PCR was performed to determine the expression levels of miR-147b and Yin Yang 1 (YY1) mRNA. CCK-8, transwell migration and wound healing assays were used to determine cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In hydrogen peroxide‐exposed cardiomyocytes, miR‐147b suppresses cell viability and promotes cell apoptosis . Moreover, miR‐147b is involved in regulating the proliferation and migration of vascular smooth muscle cells . Notably, miR‐147b has been identified as a cancer‐related miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In hydrogen peroxide‐exposed cardiomyocytes, miR‐147b suppresses cell viability and promotes cell apoptosis . Moreover, miR‐147b is involved in regulating the proliferation and migration of vascular smooth muscle cells . Notably, miR‐147b has been identified as a cancer‐related miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of YY1 inhibits the proliferation and migration of VSMCs cells and attenuates the effect of miRNA‐147b overexpression on the proliferation and migration of VSMCs. This study demonstrates that miRNA‐147b affects VSMC proliferation and migration by targeting YY1 and regulating Wnt/β‐catenin activity (Yue et al, ).…”
Section: Vsmc Proliferation Migration and Apoptosismentioning
confidence: 75%
“…Likewise, overexpression of miRNA‐365b‐3p directly targeted down‐regulation of ADAMTS1 and inhibited the proliferation of PDGD‐BB‐induced HVSMCs (Qu and Zhang, ). Yue et al () demonstrated that overexpression of miRNA‐147b enhanced the proliferation and migration of VSMCs and increased Wnt/β‐catenin signaling activity in VSMCs. By knocking down miRNA‐147b, it has been shown that the proliferation and migration of PDGF‐BB‐treated VSMCs or VSMCs were significantly inhibited.…”
Section: Vsmc Proliferation Migration and Apoptosismentioning
confidence: 99%
“…For instance, YY1 initiated the activity of the X-inactive specific transcript (Xist) promoter by directly binding to the Xist 5' region in ES cells ( 24 ). Downstream, YY1 was also revealed to be involved in the pathophysiology of AS by regulating cell proliferation and apoptosis ( 12 , 26 , 27 ). For example, a previous study reported that YY1 was involved in the promoting effects of miR-544 on the maturation and antioxidative effects of stem cell-derived endothelial-like cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its overexpression can cause the abnormal transcription of downstream genes, participating in disease occurrence, such as diabetes and B lymphoma ( 8 , 10 , 11 ). YY1 was reported to serve an important role in AS by mediating the proliferation and migration of VSMCs ( 12 ). In addition, a previous study indicated that YY1 was involved in the formation of foam cells in response to oxLDL ( 13 ).…”
Section: Introductionmentioning
confidence: 99%